10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Left atrial (LA) dysfunction may play an important role in the pathophysiology of transthyretin amyloidosis with cardiomyopathy (ATTR-CM) and is driven by LA remodeling and amyloid infiltration. OBJECTIVES: To evaluate the prognostic significance of LA structure and function among patients with ATTR-CM and to assess the effects of vutrisiran on these parameters. DESIGN, SETTING, AND PARTICIPANTS: Post hoc analyses were conducted of the HELIOS-B phase 3 randomized clinical trial, which enrolled patients with ATTR-CM between December 2019 and August 2021 at 87 sites in 26 countries. Median (IQR) follow-up was 36 (33-36) months. Data were analyzed from July through November 2025. INTERVENTIONS: Vutrisiran (25 mg subcutaneously every 3 months) vs placebo. MAIN OUTCOMES AND MEASURES: The primary outcome was all-cause mortality (ACM) and recurrent cardiovascular events. LA structure (LA volume index [LAVi]) and function (LA reservoir [LASr], conduit [LAScd], and contractile strain [LASct]) were assessed, including the effect of vutrisiran on these measures at 30 months. RESULTS: A total of 655 patients were enrolled. Among 644 patients with measurable LA strain (median [IQR] age, 77 [72-80] years; 48 female patients [7.5%]; 569 (88.4%) with wild-type ATTR), mean (SD) LA strain measures were substantially below normal (LASr: 9.5% [6.0%]; LAScd: 6.9% [3.9%]; LASct: 4.2% [4.0%]). Patients with worse LASr had more advanced disease, more atrial fibrillation, and more left ventricular systolic and diastolic dysfunction. LASr and LASct were independently associated with ACM and recurrent cardiovascular events (LASr: hazard ratio [HR] per 5% worsening, 1.37; 95% CI, 1.13-1.68; P = .002; LASct: HR per 5% worsening, 1.53; 95% CI, 1.08-2.17; P = .02), recurrent heart failure hospitalizations (LASr: HR, 1.66; 95% CI, 1.22-2.25; P = .001; LASct: HR, 2.23; 95% CI. 1.46-3.71; P < .001), and incident atrial fibrillation (LASr: HR, 1.30; 95% CI, 1.03-1.63; P = .03; LASct: HR, 2.02; 95% CI, 1.38-2.96; P < .001). In contrast, LAVi was not associated with these outcomes. LA strain measures at baseline did not modify the treatment effect of vutrisiran on ACM and recurrent cardiovascular events (LASr: P value for interaction = .60; LAScd: P value for interaction = .58; LASct: P value for interaction = .47). Vutrisiran attenuated worsening in LA strain vs placebo at month 30 (LASr: +1.2%; 95% CI, +0.4% to +1.9%; LAScd: +0.8%; 95% CI, +0.3% to +1.4%; LASct: +0.8%; 95% CI, 0% to +1.6%). CONCLUSIONS AND RELEVANCE: Per the results of this secondary analysis of the HELIOS-B randomized clinical trial, LA dysfunction is common among patients with ATTR-CM and portends a worse prognosis. Consistent with its beneficial effects on other measures of cardiac structure and function, vutrisiran attenuated worsening in LA strain at 30 months, supporting the importance of LA function in the pathophysiology of ATTR-CM and the ability of silencer therapy with vutrisiran to attenuate worsening atrial myopathy in amyloid heart disease. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04153149.